Engineering behaviour of stabilized peat soil - Sing, W.L.; Hashim, Roslan; Ali, F. (2008)
Successful implementation of deep peat stabilization is very much dependent on the engineering behaviour of stabilized peat soil. With respect to this, laboratory testing investigation on the stabilized soil often provides an indispensable guide regarding the choice, composition and dosage of binder that can be effectively applied to achieve economical deep peat stabilization. This paper discusses the evidence on the positive influence of a mixture of Ordinary Portland cement, ground granulated blast furnace slag and siliceous sand at stabilizing peat soil through laboratory investigation. Unconfined compressive strength, pH, linear shrinkage, compressibility and permeability of stabilized peat were evaluated and compared to those of untreated peat using standard soil laboratory apparatus. Markedly increase in pH and unconfined compressive strength and significant reduction in linear shrinkage, compressibility and permeability of stabilized peat were discovered from the results of the investigation.